WebPAC Interfaces : An Overview of WebPAC Interfaces in Public Libraries in Croatia - Barbarić, Ana (Array, 2002)
Web-based online public access catalogues (WebPACs) first appeared in the late 1990s and many libraries in Croatia are currently considering their implementation. As catalogues, they not only offer simplified access to library holdings, but also enable librarians to add value to catalogue data. It is very important that librarians, as information specialists, make permanent efforts to ensure that their WebPACs appear user-friendly. Only a WebPAC that is easy to use can survive and continue developing despite stiff competition among various information services and sources in the information society. Our research was an attempt to answer two questions: how user-friendly WebPAC interfaces of Croatian public libraries are and how well they make use of the advantages of their new environment – the World Wide Web. The research was conducted in December 2001 and it comprised the catalogues of the following Croatian public libraries: Medvescak Library, Zadar Public Library, “ Metel Ozegovic” Public Library and Zagreb City Libraries. The sample was obtained by dividing the ten existing WebPACs of Croatian public libraries into two strata. The first stratum is made up of six public libraries that use the same library-information system, CROLIST, which provides the same program and design solutions for their online catalogues. The second stratum consists of all the other online catalogues of Croatian public libraries. One catalogue was randomly selected from the first stratum, while the other three were randomly selected from the second stratum. Based on recent literature dealing with WebPACs and our own search experience, we came up with a list of preferable functions and features of WebPAC interfaces. The elements of WebPAC interfaces were divided into seven main categories: general features of the catalogue, interface design, search, access points and authority control, display and analysis of results, help and instructions, and, finally, circulation status of library material. The list served as a basis for assessing the usability of the WebPACs from an end-user-oriented perspective. In general terms, research results show that, in varying degrees, these catalogues do not offer many options usually associated with the concept of third-generation OPACs. Croatian public library WebPACs still rely heavily on library tradition. The possibilities of the World Wide Web have been exploited only to a lesser extent. The catalogues included in our research have been reduced to enabling access to Internet resources through bibliographic databases and to the use of hyperlinks in order to make search easier. There is also a possibility of online reservation of library material and links to catalogues of other libraries. Unfortunately, even the above-mentioned options are more exceptions than a rule, and none of our four catalogues makes full use of them. The research led us to the conclusion that Croatian public library WebPACs are only at the beginning of the process of development towards well-designed user-friendly systems.